Influência do comportamento das ligações na estabilidade de estruturas mistas de aço e concreto - Pulido, Antonio Carlos (Universidade Federal de São Carlos, 2014)
The objective of this work was to evaluate the influence of the rigidity of the beam-tocolumn connections as well as the transference of forces among the structural components in steel-concrete composite structures. to do this, data regarding the Moment vs. Rotation curve behavior of a concrete filled beam-to-column connection, previously evaluated on a different work was used for comparison. The experimental value of rigidity was inserted into models of plane frames and tridimensional models, in a way that the global stability parameters can be evaluated according to the rotational stiffness of the beam-to-column connections. In order to evaluate the stability, was led in consideration the ABNT NBR 8800:2008 Brazilian code recommendations. For the numeric simulations, the software SAP 2000® was used, in which it was simulated a plane frame model with ten floors, and also a tridimensional frame, varying the number of floors. Once constructed the numerical models, for the plane frame comparative analysis were performed study of the redistribution of forces, of consumption of steel and stability considering that the beam-to-column connections represented in the models, simulate the following situations regarding the system stiffness: rigid and semi-rigid connections and also ratios of experimental stiffness. For the tridimensional model, besides the variation of the stiffness connection the influence of number of floors on the parameters of stability and distribution of forces on structural elements was also analyzed in the present study. The results showed that the stiffness of the beam-to-connections alters the distribution of forces, and that the variation on the number of floors have influence on the global stability parameter. However, it is possible to design structures with semi-rigid beam-to-column connections respecting the normative limits for the parameters of stability and reducing the consumption of steel in the form of profiles.
Influence of the behavior of connections on the stability of concrete-steel composite structures
Keywords: Construção civil; Elementos mistos de aço e concreto; Ligações mistas; Estabilidade global; Pórticos planos; Pórticos tridimensionais; Análise estrutural; Steel-concrete composite elements; Structural analysis; Composite connections; Semi-rigid connections; Gobal stability; Plane frame; Tridimensional frame; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL